French Jewry and Agricultural Settlement in Palestine before WWI - Mayorek, Yoram (1997)
This publication is a revised version of a lecture delivered at the conference Naissance du Nationalisme Juif en Europe et en Palestine, 1880-1904 organized by the Centre de recherches arabes et hebraiques de l'Universite Charles-de-Gaulle in Lille in November 1997